Simple Method for Determination of the Number of Helicobacter pylori CagA Variable-Region EPIYA Tyrosine Phosphorylation Motifs by PCR - Argent, Richard H. (American Society for Microbiology, 2005)
Helicobacter pylori strains possessing the cag pathogenicity island are associated with the development of gastric cancer. The CagA protein is translocated into epithelial cells and becomes phosphorylated on tyrosine residues within EPIYA motifs, which may be repeated within the variable region of the protein. Strains possessing CagA with greater numbers of these repeats have been more closely associated with gastric carcinogenesis. Phosphorylated CagA leads to epithelial cell elongation, which is dependent on the number of variable-region EPIYA motifs. Thus, determination of the degree of CagA phosphorylation and the number of EPIYA motifs appears to be more important than detection of cagA alone. Determination of the number of EPIYA motifs by nucleotide sequencing, however, is a laborious and expensive process. We describe here a novel and rapid PCR method for determination of the pattern of repeats containing the EPIYA motif. This will aid in the identification of those strains that may be more likely to cause disease.